Perda dentária em adultos jovens de Santa Maria-RS: uma coorte prospectiva - Comim, Letícia Donato (2024)
Data on the oral health of adolescents and young adults are scarce in the Brazilian context and considering that this phase is a highly formative period for defining future health, it is necessary to understand the behavior patterns in this age group and the main factors that influence their oral health. This thesis is composed of three scientific articles, whose objectives were to evaluate the influence of family income trajectory on tooth loss (TL) increment (Article I), to analyze the influence of parenthood on TL increment (Article II), as well as to investigate the influence of TL in adolescence on college admission in young adults (Article III) in the city of Santa Maria, RS. This study is linked to a population-based cross-sectional epidemiological survey carried out with 1,197 adolescents aged 15 to 19 in 2018 (T1). After a mean (±standard deviation [sd]) period of 5 (±0.5) years, 570 participants with a mean (±sd) age of 22 (±1.2) years were reassessed at follow-up (T2), thus resulting in a retention rate of 47.6%. Data collection involved the application of questionnaires (contextual, sociodemographic, behavioral, and psychosocial data) and clinical dental examination (DMFT index [number of decay, missing due to caries, or filled permanent teeth]), performed at T1 and T2 by calibrated examiners. In Article I and II, TL increment was calculated as the difference between the number of missing teeth at T2 and T1, based on the M component of the DMFT index. In Article I, the main predictor variable was the trajectory of family income between the two observational moments and the outcome was TL increment (discrete variable). In Article II, the main predictor variable was having children between the two observational moments and the outcome was TL increment (binary variable). The outcome of Article III was university admission (yes or no), collected at T2, and the main predictor variable was TL prevalence at T1. Multilevel Poisson regression models were used, incidence rate ratios (IRR), relative risk ratios (RRR), and 95% confidence intervals (CI) were estimated. In the adjusted models, high income/low income and low income individuals had approximately 6 times (IRR 6.20; 95% CI 2.26-17.0) and 3 times (IRR 3.52; 95% CI 1.49-8.32) higher risks for having an additional missing tooth than their high income counterparts. No association was found between the low income/high income category and TL increment. In Article II, young adults who had children had a 2-fold greater risk for having TL increment than individuals who did not have children (IRR 2.13; 95%CI 1.04–4.36). In Article III, young adults who had at least one missing tooth in adolescence were 63% less likely to have been admitted to university between the ages of 20-24-years (RRR 0.37; 95%CI 0.15–0.90). The results of this thesis highlight the repercussions of oral health inequities on the lives of young Brazilians.